2006
DOI: 10.1029/2006gl026915
|View full text |Cite
|
Sign up to set email alerts
|

A Riccati model for Denmark Strait overflow variability

Abstract: [1] A controlled volume box model of the western basins of the Nordic Seas for water denser than 1027.8 kg m À3 is constructed, where accumulation in volume ( dV dt ) is driven by net imbalances between prescribed net inflow from the northern, eastern and top boundaries (Q s ) and hydraulically limited outflow through the Denmark Strait. The resulting Riccati equation is solved analytically for filling and flushing experiments with constant Q s and numerically for stochastic forcing Q s (t). For small perturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Just south of Fram Strait the outflowing intermediate water interacts with RAW, the southward recirculating branch of the WSC (Figure 8a). Downstream further modification of the interface height anomaly occurs due to local processes in the Nordic Seas like wind effects and deep water production [ Käse , 2006; Köhl et al , 2007; Karcher et al , 2008]. Notwithstanding these modifications, the reduced density of the exiting Arctic intermediate waters leads to an decrease in interface height north of Denmark Strait which remains over the last 15 year of the experiment (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…Just south of Fram Strait the outflowing intermediate water interacts with RAW, the southward recirculating branch of the WSC (Figure 8a). Downstream further modification of the interface height anomaly occurs due to local processes in the Nordic Seas like wind effects and deep water production [ Käse , 2006; Köhl et al , 2007; Karcher et al , 2008]. Notwithstanding these modifications, the reduced density of the exiting Arctic intermediate waters leads to an decrease in interface height north of Denmark Strait which remains over the last 15 year of the experiment (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…This is approximately 15 years. In the model the rates of replenishment of dense water in the north is simply forced by the NOA [Käse, 2006]. The interannual variability of this forcing is buffered in the Nordic Seas, leading to an accumulation of dense waters there.…”
Section: Discussionmentioning
confidence: 99%
“…Käse [2006] presented an analytical approach for the Denmark Strait overflow variability. Under the assumption that the net temporal change in the volume of dense water of the upstream basin arises from imbalances between production, inflow and controlled hydraulic outflow, a Riccati equation for the volume had to be solved (Plate 8).…”
Section: Interdecadal Overflow Variabilitymentioning
confidence: 99%
“…It has been shown that the hydraulic character of the outflow through the passages of the GISR theoretically smoothes the transport variations [ Käse , 2006]. According to this, variability on subdecadal scales are predominantly seen in local storage variations and less so in the outflow.…”
Section: Introductionmentioning
confidence: 99%